Airline investments in exclusive airport facilities: Timing decisions under demand ambiguity. (September 2020) - Zheng, Shiyuan; Fu, Xiaowen; Jiang, Changmin; Ge, Ying-En
Highlights: We analytically investigate an airlines' investment timing on its exclusive terminal under demand ambiguity. The multiple prior expected utility form and the real option approach are used to describe the airline's decision. The airline's optimal investment timing requires its expected present value of the future profit increment to exceed its investment cost by the option value multipliers. The airline's investment is later than the social optimum when the competition in the aviation market is low. The government's regulation rules on the airline's exclusive terminal investment timing indicate a stepwise structure. Abstract: In this paper, we study the timing decision of airlines' investments in exclusive airport facilities in the presence of demand ambiguity and competition. We model the investment decision as a real options problem under ambiguity. An airline's ambiguity-averse preferences are modeled using the multiple prior expected utility form. We obtain the optimal investment timing rule for the airline and find that it requires the airline's expected present value of its future incremental profit from investing to exceed the investment cost by the option value multiplier. We then compare the airline's optimal investment timing rule to the social optimum and discuss two possible subsidy policies, a lump-sum subsidy and a per-unit subsidy, with which the government can align the airline's investment timing rule with the social optimum. We characterize the stepwise structure of both subsidy policies, in which the optimal time to invest in an exclusive terminal depends on three thresholds: the social optimum, the airline's break-even point, and a combination of the social optimum and the airline optimum. We conclude that the two subsidy policies have equivalent effects when the government and the airline have the same ambiguity levels, as they lead to the same investment timing and require the same amount of government funds.